Shoulder arthroplasty - T. Bradley Edwards; Brent J. Morris; Gary M. Gartsman (Philadelphia, Pennsylvania : Elsevier, 2019)
"Focusing on all key aspects of shoulder replacement surgery and emphasizing on the latest techniques and tools, Shoulder Arthroplasty, 2nd Edition, brings you expert procedural approaches from two master surgeons in the field: Drs. T. Bradley Edwards and Brent J. Morris. Extensively illustrated, this technique-intensive reference provides step-by-step guidance on the most effective approaches to patients in everyday practice, including the variations and complications that surgeons invariably encounter. Focused, concise coverage includes indications and contraindications, preoperative planning and imaging, results and complications, and more"--Publisher's description
Keywords: Arthroplasty methods; Computer network resources; Digital Video Fulltext